Physical fitness of fourth-year medical students at Chiang Mai University - Tongprasert, Siam; Klaphajone, Jakkrit; Yaicharoen, Pongson (Biomedical Sciences and Clinical Medicine, 2024)
ObjectiveTo evaluate the physical fitness level of fourth-year medical students at Chiang Mai University. Methods The physical fitness level of fourth-year medical students was measured by the following methods: 1) body composition including body mass index and waist to hip circumference ratio, 2) lung function measurement, i.e. forced vital capacity, 3) maximal oxygen consumption, 4) flexibility, 5) hand grip strength, 6) leg strength, and 7) standing board jump. The physical fitness results of all the medical students were compared with Thai normative values. Results The number of subjects in this study was 341 students; comprising 168 males and 173 females. Physical fitness results from the methods mentioned above revealed that the medical students at Chiang Mai University had a lower level of physical fitness than the average Thai person, except for forced vital capacity and leg strength. Conclusion The findings of relatively low levels of physical fitness in medical students at Chiang Mai University possibly indicate a lack of regular physical exercises. A well-designed medical curriculum to promote more physical activities for students should be developed.